Forensic profiling of gunshot residues (GSR) from spent cartridges by solid phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) - Hui, Lim Lea (2023)
Gunshot residues (GSR) produced from different ammunitions upon firing using the same firearm could be varied according to the compositional ingredients used to make the propellant powder. Due to the introduction of non-toxic ammunition, the conventional detection of lead, barium and antimony has also reported obstacles for the confirmative determination of GSR. In such cases, the organic profiles of GSR could serve as the supporting evidence to prove a firing activity and to differentiate the ammunitions. The objective of this study was to profile the organic GSR from spent cartridges by solid phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) for forensic comparison. In this study, eleven spent cartridges were subjected to SPME-GC-MS and the chemical attribution signatures in each profile were identified. Subsequently, the organic GSR profiles across various ammunition types were compared, and lastly, a screening methodology for classification of GSR profiles was proposed. The SPME-GC-MS analysis carried on the spent cartridges had detected five key compounds, including diphenylamine (DPA), dibutyl phthalate (DBP), ethyl centralite (EC), tributyl acetylcitrate (TAC), and butyl citrate, that possessed important role in propellant powders. Comparative analysis of OGSR profiles across different ammunition types revealed the choice of stabilisers and plasticisers used were found to be varied. Based on the proposed screening methodology that employing the presence of detected OGSR compound to categorise and differentiate samples, five distinct categories were formed. By applying such screening methodology, unknown samples could be associated with potential ammunition types or distinguished based on the specific sources. To conclude, the study had successfully profile the organic GSR from spent cartridges, and the screening method could serve as a useful tool for classifying and distinguishing GSR samples, assisting forensic investigation in criminal cases involving firearm.